Neurodevelopmental disorders : DSM-5 selections (American Psychiatric Association Publishing, 2016)
This selection provides a comprehensive overview of the process of diagnosing neurodevelopmental disorders while serving as a reference guide to assist in the diagnosis of individual patients. The disorder-specific resource is an invaluable addition to the DSM-5® collection and an important contribution to the mental health profession.